1986
DOI: 10.1128/jb.165.1.21-27.1986
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, nucleotide sequencing, and expression of tetanus toxin fragment C in Escherichia coli

Abstract: The amino acid sequence of the first 30 residues of fragment C of tetanus toxin was determined, and a mixture of 32 complementary oligonucleotides, each 17 bases long, was synthesized. A 2-kilobase (kb) EcoI fragment of Clostridium tetani DNA was identified by Southern blotting and was cloned into the Escherichia coli plasmid vector pAT153 with the 32P-labeled oligonucleotide mixture as a probe. A second 3.2-kb BglII fragment was identified and cloned with the 2-kb EcoRI fragment as a probe. The nucleotide seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…Several clones were identified that hybridized to the oligonucleotides, and one clone was studied further. To cohfirm that this cloned fragment did encode part of the P.69 gene, a Sac II subfragment of the 1.9-kb Pst I fragment was purified, BAL-31-treated, and ligated into the translatiof fusion vector pWRL507 (12). Several positive recombinants were obtained when the colonies were screened by colony blotting and immunoblotting with the mAb BB05 tdata not shown; see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several clones were identified that hybridized to the oligonucleotides, and one clone was studied further. To cohfirm that this cloned fragment did encode part of the P.69 gene, a Sac II subfragment of the 1.9-kb Pst I fragment was purified, BAL-31-treated, and ligated into the translatiof fusion vector pWRL507 (12). Several positive recombinants were obtained when the colonies were screened by colony blotting and immunoblotting with the mAb BB05 tdata not shown; see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The P.93 protein was expressed in E. coli as fusion proteins either with the trpE gene product by using the vector pWRL507 (12) or with the a peptide of B-galactosidase by using the pUC vectors (11). Plasmid pWDP311 (see above) expresses an 82-kDa protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the pLPCX/TT construct, TT fragment C DNA was PCR amplified from pCR Blunt (19) to include an ATG start codon and HindIII site at the 5Ј end and a BamHI site at the 3Ј end: 5Ј primer sequence, CCGCCGAAGCT-TGCCACCATGAAAAACCTTGATTGTT; and 3Ј primer sequence, CTGT-TCGGATCCTTAGTCGTTGGTCCAA. PCR conditions were: denature at 94°C for 5 min, denature at 94°C for 1 min, anneal at 55°C for 1 min, extend at 72°C for 1 min (TaqDNA polymerase; Invitrogen); repeat the last three steps 35 times and extend at 72°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%